2005
DOI: 10.1002/nau.20133
|View full text |Cite
|
Sign up to set email alerts
|

What are the supportive structures of the female urethra?

Abstract: Aims: Female stress urinary incontinence is thought to result from impairment of the connective tissue ''ligaments'' of the urethra. Surgical repair of female incontinence mainly involves ¢xation of the urethra to the pubic bone or other surrounding structures. In the present anatomical-radiological study, the anatomy of the connective tissue structures around the female urethra was investigated to determine the anatomical structures that support the urethra and the rhabdosphincter. Materials and Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 32 publications
4
55
1
Order By: Relevance
“…Obviously, continence dysfunction is a result of anatomical and functional alterations in the bladder and urethra [145] . Although the anatomical changes regarding the urethra are established during pregnancy [146] , alterations at the receptor and cellular levels need to be clarified.…”
Section: Effects Of Hormones On Urethral Functionmentioning
confidence: 99%
“…Obviously, continence dysfunction is a result of anatomical and functional alterations in the bladder and urethra [145] . Although the anatomical changes regarding the urethra are established during pregnancy [146] , alterations at the receptor and cellular levels need to be clarified.…”
Section: Effects Of Hormones On Urethral Functionmentioning
confidence: 99%
“…Remarkably, other authors have claimed that there are no identifiable ligamentous structures fixing the urethra to the pelvic sidewall. 17 Urethral fixation (by whichever mechanism) is likely to be important for urinary continence because any 'fixation' or 'tethering' implies force (or pressure) transmission. In a subset of the population tested here we have previously been able to show that urethral mobility, as determined by UMP, is strongly associated with urodynamic stress incontinence, but not with other urodynamic diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the urogenital diaphragm for the mechanism of maintaining continence is still unknown. Many studies investigating the histomorphological and histochemical properties of striated muscles of the urethral sphincter muscle and the levator ani, regarding the control of continence, have been published [21][22][23][24][25]. Dimpfl et al [23] have shown in histomorphological studies of the pelvic floor that both aging and vaginal birth may lead to myogenic changes.…”
Section: Discussionmentioning
confidence: 99%